Houttuynia cordata Thunb. and its bioactive compound 2-undecanone significantly suppress benzo(a)pyrene-induced lung tumorigenesis by activating the Nrf2-HO-1/NQO-1 signaling pathway - Yanmei Lou; Zhenzhen Guo; Yuanfeng Zhu; Muyan Kong; Rongrong Zhang; Linlin Lu; Feichi Wu; Zhongqiu Liu; Jinjun Wu (Journal of Experimental & Clinical Cancer Research, 2019)
Abstract Background Lung cancer remains the most common cause of cancer-related deaths, with a high incidence and mortality in both sexes worldwide. Chemoprevention has been the most effective strategy for lung cancer prevention. Thus, exploring novel and effective candidate agents with low toxicity for chemoprevention is essential and urgent. Houttuynia cordata Thunb. (Saururaceae) (H. cordata), which is a widely used herbal medicine and is also popularly consumed as a healthy vegetable, exhibits anti-inflammatory, antioxidant and antitumor activity. However, the chemopreventive effect of H. cordata against benzo(a)pyrene (B[a]P)-initiated lung tumorigenesis and the underlying mechanism remain unclear. Methods A B[a]P-stimulated lung adenocarcinoma animal model in A/J mice in vivo and a normal lung cell model (BEAS.2B) in vitro were established to investigate the chemopreventive effects of H. cordata and its bioactive compound 2-undecanone against lung tumorigenesis and to clarify the underlying mechanisms. Results H. cordata and 2-undecanone significantly suppressed B[a]P-induced lung tumorigenesis without causing obvious systemic toxicity in mice in vivo. Moreover, H. cordata and 2-undecanone effectively decreased B[a]P-induced intracellular reactive oxygen species (ROS) overproduction and further notably protected BEAS.2B cells from B[a]P-induced DNA damage and inflammation by significantly inhibiting phosphorylated H2A.X overexpression and interleukin-1β secretion. In addition, H. cordata and 2-undecanone markedly activated the Nrf2 pathway to induce the expression of the antioxidative enzymes heme oxygenase-1 (HO-1) and NAD(P)H: quinone oxidoreductase 1 (NQO-1). Nrf2 silencing by transfection with Nrf2 siRNA markedly decreased the expression of HO-1 and NQO-1 to diminish the reductions in B[a]P-induced ROS overproduction, DNA damage and inflammation mediated by H. cordata and 2-undecanone. Conclusions H. cordata and 2-undecanone could effectively activate the Nrf2-HO-1/NQO-1 signaling pathway to counteract intracellular ROS generation, thereby attenuating DNA damage and inflammation induced by B[a]P stimulation and playing a role in the chemoprevention of B[a]P-induced lung tumorigenesis. These findings provide new insight into the pharmacological action of H. cordata and indicate that H. cordata is a novel candidate agent for the chemoprevention of lung cancer.